The Effect of Current Ratio and Debt to Ratio Assets Against Return on Assets - Neneng Khoiriah (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2020)
This study aims to determine the effect of Current Ratio and Debt to Asset Ratio on Return on Assets at PT. Basunanda in Jakarta. The method used was explanatory research with a sample of 85 respondents. The analysis technique uses statistical analysis with regression testing, correlation, determination and hypothesis testing. The results of this study Current Ratio influence but not significant to Return on Assets of 35.9%, the hypothesis test obtained significance of 0.286> 0.05. Debt to Asset Ratio effect but not significant to Return on Assets of 66.4%, the hypothesis test obtained significance of 0.093> 0.05. Current Ratio and Debt to Asset Ratio simultaneously influence but not significantly to Return on Assets of 69.6%, the hypothesis test obtained significance of 0.304> 0.05.